Peran Praktikum dalam Kurikulum Merdeka untuk Meningkatkan Keterampilan Mendengar Siswa Madrasah Aliyah Putri Al- Ishlahuddiny - Hikmatus Suadah (Matluba: Jurnal Pendidikan Bahasa dan Budaya Arab, 2024)
This research aims to describe the role of practicum in independent curriculum learning to improve students' listening skills. This research method uses a descriptive qualitative method. The subjects of this research are X th grade students at MA Putri Al-Ishlahuddiny. The research instrument uses documentary observation and interviews. The results of this research indicate that the implementation of practicum to improve the istima’ skills of class media